Ultrasound therapy inhibits knee osteoarthritis progression in rabbits by activating the PPARs pathway: a pilot study - Qinglu Luo; Ruike Zhang; Zhizhao Liang; Yanhua Wen; Yi Zhang; Jinyi Liu; Zhongmin Ouyang; Hongbo Wu (Annals of Medicine)
Background Ultrasound (US) is effective in knee osteoarthritis (KOA), but its therapeutic mechanism is unclear, particularly the interaction between US and peroxisome proliferator-activated receptors (PPARs). This study aims to elucidate the therapeutic mechanism of US through PPARs signaling.Methods A surgically induced KOA rabbit model evaluated the therapeutic effects of Sham US, US, Fenofibrate (PPAR-α agonist), and Rosiglitazone (PPAR-γ agonist) via MRI. Cartilage and synovium tissues were collected for immunohistochemistry, RT-PCR, and western blotting. Synovial fluid inflammatory factors were analyzed. We also developed an in vitro cultured KOA chondrocyte model to investigate the effects of US therapy on PPARs-related signaling pathways and extracellular matrix cytokines. The mechanism by which US therapy inhibits KOA was studied using GW6471 (PPAR-α antagonist) and Mifobate (PPAR-γ antagonist).Results MRI revealed that US therapy slowed cartilage thinning and improved cartilage structure in the KOA model. Concurrently, US therapy effectively reduced chondrocyte damage and degradation via modulating mRNA and protein levels of PPARs-related signaling pathways in both cartilage and synovial tissues. Additionally, US therapy suppressed synovial inflammation by downregulating pro-inflammatory cytokines such as interleukin-6, interleukin-1β, and tumor necrosis factor-α, while promoting extracellular matrix homeostasis through the upregulation of aquaporin 7 and Collagen II levels in vivo and in vitro. By maintaining cartilage-chondrocyte equilibrium, US therapy prevented GW6471 or Mifobate’s KOA-promoting impact.Conclusion Our results show that US therapy could arrest the progression of KOA by reducing synovial inflammation, delaying cartilage degradation, and decreasing extracellular matrix degradation via PPARs-related signaling pathways.